Structure of ATP synthase from an early photosynthetic bacterium Chloroflexus aurantiacus - Xin Zhang; Jingyi Wu; Zhenzhen Min; Jiamao Wang; Xin Hong; Xinkai Pei; Zihe Rao; Xiaoling Xu (Proceedings of the National Academy of Sciences, 2025)
F-type ATP synthase (F 1 F O ) catalyzes proton motive force-driven ATP synthesis in mitochondria, chloroplasts, and bacteria. Different from the mitochondrial and bacterial enzymes, F 1 F O from photosynthetic organisms have evolved diverse structural and mechanistic details to adapt to the light-dependent reactions. Although complete structure of chloroplast F 1 F O has been reported, no high-resolution structure of an F 1 F O from photosynthetic bacteria has been available. Here, we report cryo-EM structures of an intact and functionally competent F 1 F O from Chloroflexus aurantiacus ( Ca F 1 F O ), a filamentous anoxygenic phototrophic bacterium from the earliest branch of photosynthetic organisms. The structures of Ca F 1 F O in its ADP-free and ADP-bound forms for three rotational states reveal a previously unrecognized architecture of ATP synthases. A pair of peripheral stalks connect to the Ca F 1 head through a dimer of δ-subunits, and associate with two membrane-embedded a-subunits that are asymmetrically positioned outside and clamp Ca F O ’s c 10 -ring. The two a-subunits constitute two proton inlets on the periplasmic side and two proton outlets on the cytoplasmic side, endowing Ca F 1 F O with unique proton translocation pathways that allow more protons being translocated relative to single a-subunit F 1 F O . Our findings deepen understanding of the architecture and proton translocation mechanisms of F 1 F O synthases and suggest innovative strategies for modulating their activities by altering the number of a-subunit.